Mechanistic-empirical assessment of axle load legal limits on Brazilian roadways - Inoue, Danilo Keniti Nais; Fernandes Junior, Jose Leomar (Transportes, 2024)
This paper presents a comprehensive mechanistic-empirical assessment of axle load legal limits policy on Brazilian roadways, considering the intricate balance between enhanced freight transportation and potential pavement deterioration. Focusing on the prevailing flexible pavements, the study explores factors such as asphalt concrete stiffness, thickness, and axle-load increments, accounting for variations in tire-load and pressure. The analysis reveals complex relationships between these factors and their impact on pavement distress mechanisms, particularly fatigue cracking and rutting. The investigation highlights the substantial influence of axle load legal limits adjustments, even seemingly minor ones, on pavement damage, ride quality, safety, and operational efficiency. A calibrated model for assessing mechanistic-empirical load equivalency factors (LEFs) was developed, offering insights into the disparities between the model and existing empirical equations used in the Brazilian Pavement Design Guide (BPDG). This comparison underscores the potential underestimation of axle load legal limits adjustments in the current approach, emphasizing the importance of informed decision-making in transportation policy. In conclusion, this study provides critical insights for policymakers and engineers while considering axle load policy adjustments. The findings emphasize the significance of accurate engineering considerations to sustainably balance economic growth, road safety, and efficient freight transportation within Brazil’s evolving road network.